Outcomes of ABO Incompatible Kidney Transplantation: A Single Center Experience - Oliveira, Rita; Sampaio, Marco; Falavigna, Manlio; Cardoso, Daniela Henriques; Sousa, José Luís; Malheiro, Jorge; Almeida, Manuela; Martins, Maria La Salete; Bini Antunes, Marika (Brazilian Journal of Transplantation, 2023)
Background: Kidney transplantation (KT) is the treatment of choice for patients with end-stage renal disease (ESRD). General organ donor shortage remains an important limitation on KT, given the increasing number of patients waiting for transplantation. This has led to the adoption of different strategies to increase the pool of donors, such as ABO incompatible (ABOi) living KT. In this single center study, we retrospectively evaluated all donor/recipient pairs proposed for ABOi KT since the beginning of this transplantation program in our hospital in 2014. Methods: Between November 2014 and March 2022, 609 deceased donor and 223 living donor KT were performed in our center. Seventy-one donor/recipient pairs were proposed for ABOi KT and were evaluated for ABO/Rh group, Coombs tests, human leukocyte antigen (HLA) type I (A, B, C) and II (DR) high resolution genotyping and receptor to donor isoagglutinin titers and HLA antibodies. Recipients with immunoglobulins G (IgG) and/or M (IgM) isoagglutinin titers > 1:512 and/or with HLA donor specific alloantibodies (DSAs) were excluded from the ABOi transplantation program. Isoagglutinins removal was performed recurring to therapeutic plasma exchange (TPE) and/or immunoadsorption techniques. Transplanted patients were evaluated for demographic data, diagnosis, relationship with donor, sessions of antibodies removal, pre- and post-KT isoagglutinin titers, graft function, transfusion support, significant complications and overall patient survival. Results: Eighteen patients (14 males and 4 females) were transplanted with an ABOi graft out of 71 ABOi studied pairs. Median baseline IgG and IgM isoagglutinin titers were 1:32 (min 1:2, max 1:256) and 1:8 (min 1:2, max 1:32), respectively. Fifteen patients (83.3%) had pre-KT TPE and/or immunoadsorption sessions for isoagglutinin removal (mean 2.4 ± 1.8 session per patient). Seven patients (36.8%) were submitted to post-KT TPE (mean 1.9 ± 3.2 session per patient). No acute antibody mediated rejection was observed and overall graft survival was 100% on a follow-up period between 3 and 92 months (47.6 ± 25.2 months). All patients were dialysis-free with serum creatinine steady levels (median 1.4 mg/dL) at 47.6 ± 25.2 months of follow up. Conclusion: These results confirm that ABOi KT is a viable treatment for patients with ESRD, thus expanding living donor pool and reducing access time to transplantation.